Korean Association of Medical Journal Editors at the Forefront of Improving the Quality and Indexing Chances of its Member Journals - Suh, Chang-Ok; Oh, Se Jeong; Hong, Sung-Tae (Journal of Korean medical science, 2013)
The article overviews some achievements and problems of Korean medical journals published in the highly competitive journal environment. Activities of Korean Association of Medical Journal Editors (KAMJE) are viewed as instrumental for improving the quality of Korean articles, indexing large number of local journals in prestigious bibliographic databases and launching new abstract and citation tracking databases or platforms (eg KoreaMed, KoreaMed Synapse, the Western Pacific Regional Index Medicus [WPRIM]). KAMJE encourages its member journals to upgrade science editing standards and to legitimately increase citation rates, primarily by publishing more great articles with global influence. Experience gained by KAMJE and problems faced by Korean editors may have global implications.